IN VITRO BIOLOGICAL STUDY OF SEVEN NEPALESE MEDICINAL PLANTS AND ISOLATION OF CHEMICAL CONSTITUENTS FROM CISSAMPELOS PAREIRA - AMIT, MD; RAJ SHARMA, KHAGA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study aimed to investigate the phytochemical analysis and biological activities of methanol extracts of seven medicinal plants such as Anisomeles indica, Achyranthes bidentata, Sphenomeris chinensis, Cleistocalyx operculatus, Malvaviscus arboreus, Cissampelos pareira, and Tectaria coadunate collected from Tanahun district of Nepal. Methods: Phytochemical analysis was performed by color differentiation methods adopting the standard protocol. Antioxidant activity of plant extracts was evaluated by 2,2-diphenyl-1-picrylhydrazyl radical scavenging assay. Flavonoid content was estimated by aluminum chloride colorimetric method. Antidiabetic activity was evaluated by α-amylase inhibition assay where acarbose was used as standard. Toxic effect was studied by brine shrimp bioassay. Results: Phytochemical analysis showed the presence of alkaloids, polyphenols, flavonoids glycoside, and terpenoid in most of the extracts. T. coadunate and C. pareira exhibited high antioxidant activity with IC50 41.84 and 52.03 μg/ml, respectively. Whereas, the plant extracts of Malvaviscus arboretum, S. chinensis, and A. bidentata exhibited moderate antioxidant activity with IC50 76.07, 81.05, and 89.93 µg/ml, respectively. The result of flavonoid content showed the values ranged A. indica (1.84 mg quercetin equivalent per gram [mg QE/g]) to A. bidentata (5.93 mg QE/g). C. pareira and S. chinensis exhibited the highest α amylase inhibition activity with IC50 471.68 and 517.59 µg/ml, respectively. Whereas, A. indica and M. arboreus showed moderate activity with IC50 626.12 and 952.39 μg/ml, respectively. C. pareira exhibited against Staphylococcus aureus (ATCC 25923) with a zone of inhibition 12 mm/well, and Escherichia coli (ATCC 25922) 9 mm/well but, T. coadunate showed 14 mm/well against S. aureus. The plant extracts of A. bidentata and C. operculatus showed toxic effect against newly hatched brine shrimp larvae. The chemical compounds isolated from C. pareira indicated by gas chromatography-mass spectrometry analysis were 3-isopropoxy-1,1,1,7,7,7-hexamethyl-3,5,5-tris(trimethylsiloxy) tetrasiloxane, alpha-tocopherol, pentadecanoic acid, and 4,22-stigmastadiene-3-one. The major compound was indicated by percent peak area and base m/z value as alpha-tocopherol. Conclusion: Present study revealed that plant extracts are the potential source of antioxidant, antidiabetic, and antibacterial agents showing different biological activities. The results of this study provide partial scientific support for the traditional application of medicinal plants to cure diabetes and infectious diseases, although further studies are needed to assess the mechanism of action.